Rancang Bangun Prototipe Alat Penguras Air Otomatis Pada Perahu Nelayan Berbasis Mikrokontroler - Sadrina; Rosan Likwin; Baihaqi (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2025)
Poor weather is a common problem faced by fishermen. For example, heavy rain can cause boats to flood, potentially damaging the boat’s motor engine. This research is based on the problem, of designing a microcontroller-based automatic water pump prototype. The method used in the research is experimental, following the Research and Development (R&D) model. The prototype design uses a 12-volt battery to operate the Arduino as the automatic water pump system, with a 9-volt input voltage that has been converted using a step-down converter. Meanwhile, the water pump is directly connected to the battery. In testing the ultrasonic sensor as a water detector, an average discrepancy of 0.5 cm was recorded. The relay response test was conducted by supplying voltage to the relay and measuring the relay pump activation delay over a few seconds. The SMS-based notification system test, conducted using a Sim800L, showed an average response time of 0.6 seconds across five trials. This prototype can make the water draining process easier, saving time and energy, and improving efficiency.